ANALISIS PERBEDAAN KINERJA PORTOFOLIO OPTIMAL SAHAM DENGAN STRATEGI AKTIF DAN STRATEGI PASIF (Study pada indeks saham LQ45 tahun 2008-2018 ) - Mustika, Apriliyarisqi Indah; Zulfikar, Zulfikar (Universitas Nusantara PGRI Kediri, 2021)
In the capital market there are two strategies to form a portfolio, namely active and passive strategies. This study aims to determine the differences performance of the formation active stock portfolio with passive stock portfolio. The method in the formation of an active stock portfolio is single index method while passive stock portfolio uses indexing method. How to compare the performance of two portfolio strategies by calculating the return and risk obtained and performing different tests on covariance level of each portfolio with independent sample t-test. The population of this research is study on the lq45 index stock in 2008-2018. The result of this research is that active portfolio has return of 0.336% and risk of 1.106% while the passive portfolio has return of 0.339% and risk of 1.107% where both strategies have a higher level of risk than the rate of return. For the different test with independent sample t-test, it shows that the portfolios active and passive, have no significant difference in level of covariance.